OPTIMIZATION OF MULTIDIMENSIONAL CONTROL SYSTEMS FOR COMPLEXES OF ARTIFICIAL MICROCLIMATE - Голінко, Ігор Михайлович; Галицька, Ірина Євгенівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For the industrial complexes of artificial microclimate the offered method of development of complex dynamic mathematical model in space of being as an unique multidimensional object of management. Considered task of synthesis of optimum multidimensional linear-quadratic digital regulator and synthesized matrix of feed-back which after the parameters of being of object of management determines the trajectory of vector of the optimum influencing that will minimize a quadratic criterion. The offered algorithm differs by the presence of logical choice of equipment for realization of optimum management allows remind the synthesis of the automatic control system of conditioner on the basis of differentiation of the mutual influencing of regulative parameters.